Dubbing dialogues… naturally: a pragmatic approach to the translation of transition markers in dubbing - Romero Fresco, Pablo (MonTi Monografías de Traducción e Interpretación, 2014)
Although research in Audiovisual Translation is said to have come of age in the past decade, there are still several key issues that have not received the scholarly attention they deserve. In the case of dubbing, the study of the naturalness of dubbed dialogue is a case in point. The aim of the present article is to analyse the use of transition markers in dubbing in order to look precisely at the naturalness of dubbed dialogue while taking into account the dubbing constraints at play. This analysis is carried out by comparing the dubbed dialogue (English-Spanish) of a popular American sitcom to the non-translated but prefabricated dialogue of a Spanish sitcom and finally to spontaneous conversation in Spanish. The results obtained in this study suggest that the analysis of discourse markers in dubbing may yield interesting conclusions not only from a translational perspective but also from the point of view of cross-cultural pragmatics.